Commercial note issuing banks and capital market development: An empirical test of the Enskilda Banks' assets, liabilities and reserves in relation to evolving capital market liquidity in Sweden, 1834 - 1913 - Anders Ögren (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
First established during the 1830's, the Enskilda banks were characterized by unlimited owner liability and the right to issue bank notes. Consequently, in Swedish banking history, these banks have been considered to be primitive relics. This paper utilizes new data to revise this picture of the Enskilda banks. Applying Douglas W. Diamond's model (1997) of the cumulative contribution of banks to the creation of liquid asset markets in developing economies to the capital poor country of Sweden, indicates that the Enskilda banks made a contribution out of the reach of non-note issuing banks. In view of the crucial role of the Enskilda banks, the Banking Act of 1864, which effectively permitted the free establishment of such banks, must be judged to have been the most important institutional change facilitating the development of the Swedish credit market.
Keywords: E40; G21; N13; N23; 330; Banking Fragility; Capital Market Development; Classical Silver and Gold Standards; Fractional Reserves; Free Banking; Liquidity; Finanzmarkt; Goldwährung; Silberwährung; Free Banking; Bankenliquidität; Schweden